Mental health burden of persons living in Ukraine and Ukrainians displaced to Switzerland: the mental health assessment of the Ukrainian population (MAP) studies - Anja Frei; Milo A Puhan; Viktor von Wyl; Susi Kriemler; Mariya Bachmaha; Erich Seifritz; Tala Ballouz; Viktoriia Yasenok; Andreas Michael Baumer; Viktoriia Petrashenko; Marco Kaufmann; Seraina Rüegger; et al. (BMJ Global Health)
Introduction The war in Ukraine places a great burden on its population as well as the people who have been displaced from it. The aim of this study is to assess the prevalence of symptoms of depression, anxiety and Post-traumatic stress disorder (PTSD) in Ukraine and Ukrainian refugees in Switzerland and contextualise them with a non-war affected population.Methods Participants were recruited into prospective cohorts using random population sampling from 25 March to 9 August 2024. Raw prevalence estimates were adjusted using Bayesian modelling to account for instrument inaccuracy. Estimates were calculated according to age, sex and regional strata.Results 6036 Ukrainians from 10 regions, 657 refugees in Zürich and 766 Zürich residents were recruited. Prevalence of symptoms was generally high but varied across population strata in Ukraine. Median prevalence estimates for depression ranged 19.6%–54.8%; for anxiety disorder, the range was 3.7%–33.4%, and for PTSD, it was 15.0%–41.2%. We observed consistent patterns: (1) The burden was higher in south-east and central Ukraine than in the north-west; (2) refugee mental health closely resembles that of south-eastern and central Ukraine; (3) prevalences among women were higher than for men across conditions.To contextualise differences in mental health burden, we highlight the example of the group of old women aged 25–44 years. We found a prevalence of depression of 11.1% (95%CI: 4.6% to 19.6%), anxiety 3% (0.5% to 9.5%) and PTSD 4.8% (1.3% to 10.6%) in Zurich residents and a prevalence of depression of 46.9% (39.4% to 59.8%), anxiety 25.2% (19.8% to 31.3%) and PTSD 33.9% (28.7% to 39.4%) in women from Central Ukraine.Conclusions This first large-scale population-based study highlights a significant mental health burden among adult Ukrainians across the age range, in Ukraine and in Zurich compared with a non-war affected general population. These findings inform the planning and evaluation of urgently needed public mental health and mental healthcare services while also aiming to destigmatise mental health disorders by highlighting the substantial impact on the civilian population.Trail registration number ISRCTN17240415.